Daya Dukung Lahan dan Daya Dukung Permukiman dengan Pendekatan Kemampuan Lahan di Kecamatan Sragen dan Kecamatan Sambungmacan Kabupaten Sragen - Hadi Wiwit Hadi Hendro Cahyono; Rahning Utomowati; Rita Noviani (Jurusan Perencanaan Wilayah dan Kota, 2022)
Abstract: Utilization of land as space for living has the capacity or power to support this use. The carrying capacity of the land is based on the capacity of the area in general land use for consideration. The research objective is to see the carrying capacity and carrying capacity based on the application basis. Data analysis techniques using scoring and overlay methods. The results showed that the carrying capacity of the land was very high, dominating the research area with an area of 6,875.2 ha or 96.30%. The carrying capacity of settlements in Sragen and Sambungmacan Districts is determined by the optimal housing carrying capacity and high housing carrying capacity. The status of the carrying capacity of settlements contained in the research area is due to differences in the total area that is suitable for settlement and the number of inhabitants.